Examine the effect of setting time and compressive strength of cement mortar paste using iminodiacetic acid. (2020) - Sharma, Prashant; Sharma, Neha; Singh, Prakash; Verma, Mohit; Parihar, Hemant Singh
Abstract: Herein we are reporting the effect of iminodiacetic acid (IDA) on setting time as well as compressive strength of cement mortar paste. The compressive strength test and setting time test have been performed using IDA with OPC by changing the percentage of IDA i.e.; the IDA dosages were used 0.05%–2.0% by weight of cement. The lesser formation of CSH is observed for IDA content beyond 1.25%. Test results revealed that IDA influences setting time and retards the setting time of cement paste up to 10 h. This retarding effect can be achieved by adjusting the percentage of IDA. This prolonged setting time is beneficial for producing flowing concrete & transportation where mixing and placing time is more than five hours especially in hilly region. Compressive strength of cement has been examined as cube strength with curing stages of 3, 7 and 28 days. From the results obtained it was that the IDA can be used for the lengthening the initial setting time with slightly decreasment in compressive strength of cement mortar paste.